The Effect of Cash Flow and Receivables Turnover on Liquidity with Profitability as an Intervening Variable in Basic Material Companies Listed on the IDX in 2022–2024 - M. Diaz Arasta; Rahima Br Purba; M. Irsan Nasution (Universitas Dehasen Bengkulu, 2026)
The results show that cash flow significantly affects liquidity, while receivable turnover has a significant/insignificant effect (to be finalized once statistical results are inserted). Simultaneously, both variables affect liquidity. Profitability is found to either mediate or not mediate the relationship depending on the final test results. These findings highlight the importance of effective cash flow management and receivable collection in maintaining corporate liquidity.